Construction of Sustainable Territories and the Multiple Dimensions of Sustainability: An Assessment of Urban and Environmental Instruments in the Juqueri-Cantareira Sub-basin of the São Paulo Metropolitan Region - Marques, Andresa Ledo; Alvim, Angélica Tanus Benatti (Frontiers in Sustainable Cities, 2021)
This article explores the relationship between legal frameworks, urbanization and environment in the context of metropolitan fringes. The focus of study is the Juqueri-Cantareira sub-basin, a strategic territory for the ecosystemic balance of the São Paulo Metropolitan Region (SPMP), Brazil. This region is also home to critical natural remnants and watersources protected by Law and encompasses smaller cities undergoing intense urbanization out of step with prevailing instruments of urban and environmental planning. The article examines the limits and challenges of the urban and environmental instruments proposed for a section of the Juqueri-Cantareira sub-basin, particularly those lying within the protected area for Spring recovery (Alto Juquery). It is assumed that municipal Master Plans and the Specific Law for Protection and Recovery of Springs (State Law 15.790/2015) should be within the framework of an integrated planning process, in which sustainability is systemic and has multiple dimensions. A qualitative assessment methodology was adopted that covers four dimensions of sustainability (political, environmental, territorial and socioeconomic) in an analysis of the urban instruments of the cities of Caieiras, Franco da Rocha and Mairiporã, and of the environmental instrument - the Specific State Law for the Protection and Recovery of Springs. The study sought to determine how these instruments articulate and incorporate these dimensions to promote strategies contributing to sustainable development and addressing socio-spatial inequalities in the region. The results revealed that, although the instruments analyzed addressed, to a greater or lesser extent, the dimensions of sustainability defined for the study, a sectoral fragmented view prevailed, as did the model of a sprawling city. The planning process should be reviewed to provide an integrated vision of regional scope to value the territory, environmental heritage and local communities, favoring their sustainable development.